2009
DOI: 10.2214/ajr.09.2377
|View full text |Cite
|
Sign up to set email alerts
|

Cysts Within and Adjacent to the Lesser Tuberosity and Their Association With Rotator Cuff Abnormalities

Abstract: Cysts located within the lesser tuberosity are rare and are indicative of subscapularis and supraspinatus tendon abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
(32 reference statements)
1
23
1
1
Order By: Relevance
“…Prior studies have reported different degrees of relationship between the two. 6,[22][23][24] Regardless of the findings reported by the prior studies, those studies differed in statistical design from the current study. Two prior studies compared the frequency of LT cysts in SBT groups and in normal SBT groups, using w 2 tests.…”
Section: Discussionmentioning
confidence: 63%
“…Prior studies have reported different degrees of relationship between the two. 6,[22][23][24] Regardless of the findings reported by the prior studies, those studies differed in statistical design from the current study. Two prior studies compared the frequency of LT cysts in SBT groups and in normal SBT groups, using w 2 tests.…”
Section: Discussionmentioning
confidence: 63%
“…Sixteen studies (53%) were conducted prospectively; one study did not mention time of enrollment. Ten studies reported abnormalities in asymptomatic volunteers 1,11,16,18,21,23,24,33,39,47 ; 5 studies (4 of which were cadaver studies) reported prevalence in the general population 10,14,26,28,49 ; 8 included symptomatic patients 6,7,31,36,44,46,50,51 ; and 7 described patients with acute or chronic shoulder dislocations. 3,27,29,38,42,43,52 The majority of the studies used ultrasound to image the rotator cuff (43%; 13 of 30).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The axillary view can show alterations of the lesser tuberosity, such as irregularities or cysts, which argue in favour of a SSC tendon lesion [21]. Anterior subluxation of the humeral head can also be seen on this view [22].…”
Section: Radioanatomymentioning
confidence: 99%